Oblique Lumbar Interbody Fusion Using a Stand-Alone Construct for the Treatment of Adjacent-Segment Lumbar Degenerative Disease - Kai, Wang; Cheng, Cheng; Yao, Qingyu; Zhang, Can; Jian, Fengzeng; Wu, Hao (Frontiers in Surgery, 2022)
Objective Adjacent-segment disease (ASD) is common in patients undergone previous lumbar fusion. A typical revision treatment from posterior approach requires management of postoperative scar tissue and previously implanted instrumentation. An oblique lumbar interbody fusion (OLIF) approach allows surgeon to reduce the potential risk of posterior approach. This study aimed to analyze the clinical and radiographic efficacy of stand-alone OLIF for the treatment of lumbar adjacent-segment disease. Methods A total of 13 consecutive patients who underwent stand-alone OLIF for the treatment of adjacent-segment disease from December 2016 to January 2019 were reviewed. Visual analog scale (VAS) of back pain and leg pain and the Oswestry Disability Index (ODI) before surgery and at last postoperative clinic visits were obtained. Radiography, CT and MRI before and at last follow-up after surgery was evaluated in all patients. Results During the study period, 13 cases were successfully treated with stand-alone OLIF. The mean follow-up was 17.7 ± 8.3 months. The back pain VAS improved from 6.2 ± 1.0 to 2.0 ± 1.1 (P < 0.01), and the leg pain VAS improved from 7.0 ± 1.9 to 1.0 ± 0.9 (P < 0.01). ODI improved from 28.0 ± 7.5 to 10.8 ± 4.0 (P < 0.01). The disc height (DH) increased from 9 ± 2 to 12 ± 2 mm (P < 0.01), the cross-sectional area (CSA) of spinal canal increased from 85 ± 26 to 132 ± 24 mm2 (P < 0.01), the foraminal height increased from 17 ± 2 to 21 ± 3 mm (P < 0.01) and the CSA of foramen increased from 95 ± 25 to 155 ± 36 mm2 (P < 0.01). Cage subsidence was observed in 2 cases. Conclusions Stand-alone OLIF provides a safe and effective alternative way to treat ASD.